PROFITABILITY AND STRATEGY OF PALM OIL PARTNERSHIP: CASE STUDY IN PT ABC - Garry Christ Himawan; Aria Farah Mita (AKUNTABILITAS, 2023)
Oil palm partnerships between commercial companies and smallholders have been going on since the 1980s. Although the partnership is intended to provide benefits for both parties, there are still many problems. Research on the problems of nucleus-plasma partnerships from the perspective of oil palm companies is still limited, so it needs to be done. This study aims to find the root cause of partnership problems carried out by Company ABC as well as to provide a business strategy to generate sustainable and mutually beneficial partnerships. The research was conducted by looking for the root causes of the low profitability of partnerships conducted with farmers, then looking for solutions to each of the root causes and at the same time strengthening the variables that affect farmer commitment and trust in partnerships. This study using institutional logic theory to evaluate Company ABC's oil palm program partnerships and key mediating variables models from commitment and trust theory to develop strategy. The results of this study include seven points of the root causes within the partnership and three points of the root causes outside the partnership as well as nine points of strategic advice that are expected to increase partnership profitability for ABC companies.